Estudio de almacenamiento para determinar la vida útil de tres bebidas ancestrales fermentadas de bajo contenido alcohólico. - Arias Quispe, Andrea Michelle (2020)
The storage study to determine the shelf life of three fermented ancestral beverages of low alcohol content was carried out to establish the storage time in PET and glass containers at temperatures of (20 °C and 4 °C) before heat treatment. An experimental design was performed with a 3 × 2 × 2 factorial arrangement with 2 repetitions under a completely randomized block design (DBCA), where the factors were: Factor A (types of "chicha"), Factor B (types of packaging), and Factor C (Storage temperatures), 12 treatments were obtained. The physicochemical parameters that were evaluated are pH, acidity, ° Brix, ° alcohol, and microbiological analysis of molds and yeasts; the data were taken every three days for 21 days. It was determined that the best treatments were white "chicha2 with a PET container at 4 °C with a pH 4.36, called acidity 0.10%, Brix ° 3.15, alcoholic strength of 2.00 v / v, count of molds and yeasts <10 CFU and 68% acceptability. For black "chicha" with glass container at 4 ° C, with a pH of 4.93, called acidity 0.30%, Brix ° of 8.40, alcoholic strength of 3.80 v / v, mold and yeast count < 10 CFU and 78% acceptability. Finally, for wiwis "chicha" with glass container at 4 ° C with a pH of 4.98, called acidity 0.29%, Brix 6.00, alcoholic strength 2.60 v / v, mold and yeast count <10 CFU and 78% acceptability. Bromatological and microbiological analyses were performed. For white "chicha" with a 0.27% protein, potassium (39.73 ± 3.34 mg / 100g), mesophilic aerobic count, mold count, yeast (<10 CFU / ml). For black "chicha" with a 0.45% protein, potassium 59.60 ± 5.01 mg / 100g, mesophilic aerobic count, mold count, yeast (<10 CFU / ml). Finally, for wiwis "chicha" with a 0.37% protein, potassium 32.68 ± 2.75 mg / 100g, mesophilic aerobic count, mold count, yeast (<10 CFU / ml). It was concluded that the type of packaging and temperature have significance; also, the estimated shelf life of the three drinks is between 9 to 12 days.